Applied Computational Intelligence and Mathematical Methods Computational Methods in Systems and Software 2017, vol. 2 - Silhavy, Radek; Silhavy, Petr; Prokopova, Zdenka (Advances in Intelligent Systems and Computing, 2018)
The book discusses real-world problems and exploratory research in computational intelligence and mathematical models. It brings new approaches and methods to real-world problems and exploratory research that describes novel approaches in the mathematical methods, computational intelligence methods and software engineering in the scope of the intelligent systems. This book constitutes the refereed proceedings of the Computational Methods in Systems and Software 2017, a conference that provided an international forum for the discussion of the latest high-quality research results in all areas related to computational methods, statistics, cybernetics and software engineering.